Sistem Pakar Diagnosis Awal Penyakit Anemia Menggunakan Metode Naïve Bayes dan Certainty Factor - Yustika Maulina; Aris Gunaryati; Rima Tamara Aldisa (Universitas Indraprasta PGRI Jakarta, 2023)
In Indonesia, anemia is a common blood disorder. The absence of red blood cells in the body can cause the disease. The large number of people who still ignore the early symptoms of anemia can worsen the body's condition due to delays in diagnosing the disease they are experiencing. This study will combine the Naïve Bayes and Certainty Factor methods in assisting the initial diagnosis of anemia. The Naïve Bayes method is used to determine the type of anemia a user suffers from based on the symptoms they have. After that, the system will perform a calculation using the Certainty Factor method based on the type of disease that has been determined previously to find out how much the certainty to prove that the user has anemia. A Test on the system produce an accuracy score of 93% from 60 test data.